2002
DOI: 10.1093/hmg/11.7.823
|View full text |Cite
|
Sign up to set email alerts
|

The Leber congenital amaurosis gene product AIPL1 is localized exclusively in rod photoreceptors of the adult human retina

Abstract: Leber congenital amaurosis (LCA) is the most severe inherited retinal dystrophy resulting in markedly impaired vision or blindness at birth. LCA is characterized by an extinguished electroretinogram in infancy, which is thought to be indicative of an early and severe impairment of both the rod and cone photoreceptors in the human retina. Recently, the aryl hydrocarbon receptor-interacting protein-like 1 (AIPL1) gene was identified as the fourth causative gene of LCA. AIPL1 encodes a 384 amino acid protein of u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
61
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(64 citation statements)
references
References 39 publications
3
61
0
Order By: Relevance
“…By immunohistochemistal studies, we demonstrated that the immunoreactive AIPL1 is present in both the developing and mature photoreceptors of the retina and that its subcellular localization overlaps with that of NUB1. The immunolocalization within the adult retina identified here is consistent with the recent results of van der Spuy et al (21), who demonstrate that AIPL1 localizes to both the cytoplasm and the nucleus of the photoreceptor cells of the retina, and E. Deery et al (manuscript in preparation), who also observe localization of the protein in the nucleus and cytoplasm of cultured mammalian cells. Moreover, the high perinuclear concentration of AIPL1 in the differentiated retina suggests that it may function similarly to AIP, in cytoplasmic stability and trafficking its target, such as NUB1, to the nucleus (7)(8)(9)(10)(11)(12)(13)(14)(15).…”
Section: Discussionsupporting
confidence: 91%
“…By immunohistochemistal studies, we demonstrated that the immunoreactive AIPL1 is present in both the developing and mature photoreceptors of the retina and that its subcellular localization overlaps with that of NUB1. The immunolocalization within the adult retina identified here is consistent with the recent results of van der Spuy et al (21), who demonstrate that AIPL1 localizes to both the cytoplasm and the nucleus of the photoreceptor cells of the retina, and E. Deery et al (manuscript in preparation), who also observe localization of the protein in the nucleus and cytoplasm of cultured mammalian cells. Moreover, the high perinuclear concentration of AIPL1 in the differentiated retina suggests that it may function similarly to AIP, in cytoplasmic stability and trafficking its target, such as NUB1, to the nucleus (7)(8)(9)(10)(11)(12)(13)(14)(15).…”
Section: Discussionsupporting
confidence: 91%
“…AIPL1 is expressed selectively in the retina and the pineal gland (3,5). AIPL1 shares high sequence homology (49% identity) and similar domain organization with the ubiquitously expressed aryl hydrocarbon receptor-interacting protein (AIP) (3).…”
mentioning
confidence: 99%
“…AIPL1 expression has been detected in both rods and cones during retinal development while in the differentiated retina expression seems restricted to rod photoreceptors. 13,14 Although it has been hypothesized that AIPL1 expression in cones is restricted to the retinal developmental period, very recent findings have shown that AIPL1 is expressed in human adult cones, where it may function to preserve cone activity and survival. 15 Successful AIPL1 retinal gene transfer using adeno-associated viral (AAV) vectors has been achieved in two different AIPL1 mouse models, 16,17 suggesting that this strategy can be potentially applied to LCA4 patients.…”
mentioning
confidence: 99%